APPLICATION OF MARKETING IN FORMAL EDUCATION AS A STRATEGY OF DEFENDING THE EXISTENCE OF THE ISLAMIC BOARDING SCHOOL - Sopwandin, Iwan (Al-Mubin, 2024)
In the present day, Islamic educational institutions face intense competition, particularly from traditional establishments, due to the emergence of modern educational institutes that provide curricula and novel systems, such as the integration of formal education. This motivates conventional educators to devise strategies for sustaining their operations amidst this intense competition. In light of the fact that contemporary society tends to favor educational institutions that combine formal education and religion. The Pondok Pesantren Miftahul Ulum Mount bubut, Tasikmalaya is also concerned with how to ensure its continued existence through the establishment of formal education. Subsequently, this study was conducted in an effort to assess the viability of formal education as a means of preserving the Miftahul Ulum Pondok Pesantren. Utilizing a descriptive analysis approach and qualitative research methodology, data is gathered via documentation studies, interviews, and observations. Subsequently, the data is analyzed through an interactive model comprising the following stages: data condensation, data presentation, and conclusion. The results of the study indicated that the Mifatahul Ulum Pondok Pesantren implemented a formal education initiative in order to ensure its continued existence. This was accomplished through the establishment of the Yapim SMK, which offered two disciplines. The school utilized the mix marketing approach to introduce and promote its offerings. These included an Islamic environment, extracurricular activities, entrepreneurial pursuits, affordable prices, sufficient facilities, a strategic location, a connection between the school curriculum and training, and the promotion of special rates for students who participated in the training